2020
DOI: 10.1186/s12874-020-01136-2
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting men from across the socioeconomic spectrum via GP registers and community outreach to a weight management feasibility randomised controlled trial

Abstract: Background Men, particularly those living in disadvantaged areas, are less likely to participate in weight management programmes than women despite similar levels of excess weight. Little is known about how best to recruit men to weight management interventions. This paper describes patient and public involvement in pre-trial decisions relevant to recruitment and aims to report on recruitment to the subsequent men-only weight management feasibility trial, including the: i) acceptability and fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In the Healthy Dads Healthy Kids feasibility study in the UK, individual and focus group interviews with fathers and other family members from a range of ethnic, religious, and socioeconomic groups informed the cultural adaptation of the programs, with patient and public involvement also integrated throughout 99 . In the “Game of Stones” feasibility trial of a remotely delivered individual intervention in Scotland, a focus group with men from lower socioeconomic areas informed the recruitment strategies; with a large survey, and patient and public involvement activities undertaken to inform the intervention design and study processes 41,102 . Eleven (30.6%) trials did not report intervention tailoring for men or undertake stakeholder or target group consultations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Healthy Dads Healthy Kids feasibility study in the UK, individual and focus group interviews with fathers and other family members from a range of ethnic, religious, and socioeconomic groups informed the cultural adaptation of the programs, with patient and public involvement also integrated throughout 99 . In the “Game of Stones” feasibility trial of a remotely delivered individual intervention in Scotland, a focus group with men from lower socioeconomic areas informed the recruitment strategies; with a large survey, and patient and public involvement activities undertaken to inform the intervention design and study processes 41,102 . Eleven (30.6%) trials did not report intervention tailoring for men or undertake stakeholder or target group consultations.…”
Section: Resultsmentioning
confidence: 99%
“… 99 In the “Game of Stones” feasibility trial of a remotely delivered individual intervention in Scotland, a focus group with men from lower socioeconomic areas informed the recruitment strategies; with a large survey, and patient and public involvement activities undertaken to inform the intervention design and study processes. 41 , 102 Eleven (30.6%) trials did not report intervention tailoring for men or undertake stakeholder or target group consultations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Game of Stones (GoS) is a parallel, 3-arm RCT that delivers automated Short Messaging System (SMS) texts over a 1-year period, with or without financial incentives, and compares weight change at 12 months (M) from baseline with a waiting list comparator group, for men living with obesity. The GoS feasibility study was over-subscribed and demonstrated broad acceptability, and 60% of the 105 men participating lived in the two most disadvantaged Scottish Index of Multiple Deprivation (SIMD) postcode quintiles, a higher proportion than in other UK obesity trials [ 13 15 ]. Fewer men living in disadvantaged areas dropped out compared to men living in more advantaged areas.…”
Section: Introductionmentioning
confidence: 99%